Towards a Better Understanding of Nutritional and Therapeutic Effects of Honey and Their Applications in Apitherapy - Alexandra-Antonia Cucu; Gabriela-Maria Baci; Adela Ramona Moise; Ştefan Dezsi; Bianca Dana Marc; Ştefan Stângaciu; Daniel Severus Dezmirean (Applied Sciences, 2021)
The nutritional and therapeutic aspects of natural products have gained more interest in recent years, owing to the importance that has been given to health and well-being. In this regard, honey represents an organic product whose high level of biologically active compounds and valuable nutrients have been extensively studied in order to prove its ability to provide an enhancement in health status. The use of honey in the process of healing or preventing certain diseases has been practiced throughout history and is now known as apitherapy. The aim of this review is to expand the knowledge and understanding towards the physicochemical characteristics of honey and the action of its main bioactive compounds towards health-beneficial properties (antioxidant, antimicrobial, antifungal, antiviral, etc.) for apitherapeutic purposes. Notwithstanding all the assets, the usage of honey for medical purposes encounters some limi-tations regarding the factors that may affect the therapeutic potential of honey in apitherapy that will be pointed out in this overview.